Do high income households reduce driving more when living near rail transit?. (March 2020) - Boarnet, Marlon G.; Bostic, Raphael W.; Rodnyansky, Seva; Burinskiy, Evgeny; Eisenlohr, Andrew; Jamme, Huê-Tâm; Santiago-Bartolomei, Raúl
Highlights: Rail TOD residence is associated with larger VMT reductions at higher incomes. Differences in transit trips, far vs. near rail, are similar at high and low incomes. VMT decreases most, far vs. near rail, at higher incomes in employment-dense TOD. For all distances <4 miles, moving closer to rail TOD is associated with lower VMT. Abstract: Transportation planning today requires an understanding of how income and near-rail residence jointly influence household travel behavior. This article fills a gap in the literature by showing how vehicle miles traveled (VMT) and transit trips taken (TT) vary with income and rail transit access by neighborhood type. Results indicate that, when comparing households with similar incomes and examining how the "near-rail" versus "far from rail" VMT and TT gap varies by income, the cross-sectional reduction in nominal VMT and the increase in TT on a percentage basis is generally larger for higher-income households (>$50, 000), and particularly so in neighborhoods dense with both jobs and population. These findings offer support for the notion that near-transit housing targeting higher-income households can have both sustainability and transit use benefits. We note, though, that equity considerations are a strong reason to include low-income housing near rail transit, and argue that policies focusing overly singly on either low-income or high-income housing near rail transit will not be as impactful as a robust focus on mixed-income housing developments in rail transit-oriented developments (TODs).